1997
DOI: 10.1016/s0022-5223(97)70332-5
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of injury in canine lung grafts by exogenous surfactant therapy

Abstract: Instillation of surfactant before mechanical ventilation reduced protein leak, maintained a low surfactant small to large aggregate ratio, and prevented a decrease of oxygen tension in donor animals. After transplantation, surfactant-treated grafts had superior oxygen tension values and a higher proportion of superiorly functioning surfactant aggregate forms in the air space than untreated grafts. Exogenous surfactant therapy can protect lung grafts from ventilation-induced injury and may offer a promising mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
1
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 25 publications
3
37
1
1
Order By: Relevance
“…Several studies have identified the important role of surfactant alterations in transplantationrelated I/R injury of the lung [8,9,[35][36][37][38][39][40]. Accordingly, exogenous surfactant therapy has been applied successfully in experimental [12][13][14][15][16][17][18][19][20][21] and clinical [22][23][24] studies. It is, therefore, considered a potentially promising therapy for the mitigation of severe lung I/R injury, although the optimal surfactant preparation and mode of therapy still need to be determined [26,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have identified the important role of surfactant alterations in transplantationrelated I/R injury of the lung [8,9,[35][36][37][38][39][40]. Accordingly, exogenous surfactant therapy has been applied successfully in experimental [12][13][14][15][16][17][18][19][20][21] and clinical [22][23][24] studies. It is, therefore, considered a potentially promising therapy for the mitigation of severe lung I/R injury, although the optimal surfactant preparation and mode of therapy still need to be determined [26,41].…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental [12][13][14][15][16][17][18][19][20][21] and clinical [22][23][24] studies give evidence that exogenous surfactant therapy successfully supplements the imbalanced endogenous surfactant system, serving to attenuate I/R injury and effectively improve lung preservation and graft function [11]. The great advantage of exogenous surfactant therapy of the donor in human lung transplantation is the fact that PGD in this case can accurately be predicted and, thus, even be prevented, providing a promising approach for prophylactic surfactant therapy [11,25,26].…”
mentioning
confidence: 99%
“…The grafts were stored for 17 h and then retransplanted and reperfused for 6 h. The lung grafts treated with surfactant showed much better oxygenation (mean PaO 2 /FIO 2 307 AE 63 mmHg vs 73 AE 14 mmHg in untreated grafts) and a lower small/large surfactant aggregate ratio. These findings indicated that exogenous surfactant therapy may protect lung grafts from ventilationinduced injury [11]. Accordingly, Hausen et al [12] in a double-lung transplant model with 16 h of ischemia, found that porcine surfactant replacement therapy in the donor before organ perfusion significantly enhanced graft function after extended ischemia.…”
Section: Discussionmentioning
confidence: 97%
“…Three years later, the same group [11] reported the administration of bovine lipid extract surfactant to 5 donor dogs (5 controls) that underwent prolonged (8 h) mechanical ventilation. The grafts were stored for 17 h and then retransplanted and reperfused for 6 h. The lung grafts treated with surfactant showed much better oxygenation (mean PaO 2 /FIO 2 307 AE 63 mmHg vs 73 AE 14 mmHg in untreated grafts) and a lower small/large surfactant aggregate ratio.…”
Section: Discussionmentioning
confidence: 99%
“…As alterações na complacência pulmonar provocam um quadro de dispnéia, amplificação da resistência vascular das vias aéreas, aumenta o espaço morto e do shunt intrapulmonar, hipercapnia ou hipocapnia, alcalose respiratória e hipoxemia (SANTOS et al, 2000;KOSHIKA et al, 2001;BIGATELLO;DAVIGNON;STELFOX, 2005 (WABG et al, 2002;GRENE et al, 1999;NOVICK et al, 1997). …”
Section: Revisão De Literaturaunclassified